Myeloid Blast Crisis in A 15 Years Adolescent Under Treatment for CML - Bhandari, Isha; Sharma, Krishna Sagar; Tiwari, Niva; Adhikari, Sudhir; Yadav, Ram Krishna (Journal of College of Medical Sciences-Nepal, 2025)
Background Chronic myeloid leukemia is relatively a rare haematological malignancy to present during childhood. CML is classically staged into three progressive phases - chronic, accelerated, and blastic. Blastic phase is the most critical phase likely to be fatal within few months. However, most children (95%) present in the chronic phase and are managed with oral tyrosine kinase inhibitor weighing the risk benefit ratio of toxicities during and after the Hematopoietic Stem Cell Transplantation. The main aim of treatment is to hault the progression to blast crisis. We report a case of 15 years’ adolescent presented with huge splenomegaly and leucocytosis with 100% BCR-ABL fusion gene positive managed with Imatinib. He developed myeloid blast crisis even being on regular therapy with imatinib within 18 months. He survived the phase with meticulous investigations and management. Here we highlight the importance of HSCT for the eradication of the disease process even in those who were considered TKI responsive.